Local Potential Development (Local Genius) in Community Empowerment - Hidayat, Dayat; Syahid, Ahmad (Journal of Nonformal Education, 2019)
Community entrepreneurship training is one of strategies to improve community economic empowerment. Entrepreneurship training is carried out to improve the ability of the learners to develop their business. This program was carried out because the community's entrepreneurial ability in the CLC Assolahiyah in Karawang regency was still deficient. The aim of this research is to describe the identification of local resources in the development of entrepreneurship for community empowerment through training and mentoring the community entrepreneurship. The approach in this research is qualitative. Research method used is case study to describe local potential development in community empowerment. Data collection techniques used are observation, interview, and documentation study. Data analysis techniques are interactive models, through the stages of data collection, data reduction, display data, conclusions, and verification. The result concludes that the development strategy of community entrepreneurial program begins with the identification of local potential resources, both natural resources and human resources. The results of the entrepreneurship training are the growth and development of productive skills, technical skills, physical skills, social skills, managerial skills, and intellectual skills of the learner’s entrepreneurship. The impact of developing local potentials in implementing entrepreneurship programs is increasing the empowerment of community entrepreneurship. The indicator is the increase of independence, community empowerment and economic income generation.